2011
DOI: 10.1007/s11738-011-0789-6
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with arbuscular mycorrhizal fungus affects growth, drought tolerance and expression of stress-responsive genes in Poncirus trifoliata

Abstract: The objective of this study was to investigate the effects of arbuscular mycorrhizal fungus (AMF) inoculation on growth and drought tolerance of Poncirus trifoliata seedlings. The seedlings were inoculated with or without Glomus mosseae before exposure to a short-term (3 days) water depletion, and relevant physiological and biochemical parameters (plant height, chlorophyll content, relative water content, activity of antioxidant enzymes) and expression patterns of several stress-responsive genes were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 37 publications
4
38
1
1
Order By: Relevance
“…An accumulation of proline in ''H2'' cultivar may also play a key role as osmolyte to control the water relation in the water deficit condition. Earlier, similar observations were made in drought stressed Poncirus trifoliata plants wherein proline accumulation was greater in AM-associated plants than in non-AM-inoculated plants (Fan and Liu 2011). The horizontal growth in the AMassociated plant of ''H2'' cultivar under drought stress suggests an effective relationship of energy-signals/substrates, e.g.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…An accumulation of proline in ''H2'' cultivar may also play a key role as osmolyte to control the water relation in the water deficit condition. Earlier, similar observations were made in drought stressed Poncirus trifoliata plants wherein proline accumulation was greater in AM-associated plants than in non-AM-inoculated plants (Fan and Liu 2011). The horizontal growth in the AMassociated plant of ''H2'' cultivar under drought stress suggests an effective relationship of energy-signals/substrates, e.g.…”
Section: Discussionsupporting
confidence: 70%
“…Previously, it has been demonstrated that proline accumulation under drought is lower in leaves of AM plants than in non-AM plants of C. tangerine (Wu and Xia 2006), E. variegata (Manoharan et al 2010), P. vera (Abbaspour et al 2011), pigeon pea (Qiao et al 2011) and snapdragon (Asrar et al 2012). Such a mechanism has been linked to the protection of host plants from dehydration stress through primary drought avoidance mechanisms (Fan and Liu 2011). The avoidance mechanism of AM plant in ''660'' cultivar may lead to high accumulation of soluble carbohydrates and low water content, which need no energy for growth, leads to storage of sugars, and results in growth promotion under drought.…”
Section: Discussionmentioning
confidence: 98%
“…The enhanced accumulation of proline in these studies was linked to AM-induced drought resistance with proline acting as osmoprotectant. Conversely, in several studies, while proline content increased in response to water deficit, a lower accumulation of proline has been observed in mycorrhizal plants relative to nonmycorrhizal counterparts (RuizLozano and Azcón 1997; Wu and Xia 2006;Aroca et al 2008;Ruiz-Sánchez et al 2010;Abbaspour et al 2012;Fan and Liu 2011;Asrar et al 2012;Doubková et al 2013), suggesting that AM symbiosis enhanced host plant resistance to drought.…”
Section: Role Of Metabolic Changes In Osmoregulationmentioning
confidence: 96%
“…A number of studies have confirmed that AM fungi can enhance the drought tolerance of various plants species678. The potential mechanisms are: (1) direct water absorption by extraradical hyphae910, (2) increase in nutrient uptake, especially P11, (3) biochemical changes in osmotic adjustment and antioxidant defence systems1213141516, (4) improvement of the soil structure by glomalin-related soil proteins of AM fungi17, and (5) changes in molecule levels, including aquaporins71819, genes involved in oxidative stress20 and proline synthesis21, dehydrin proteins22, and genes involved in stomata development and ABA responses or encoding proteins involved in plant response pathways2324. The underlying mechanisms of phytohormone responses and root adaptation need to be elucidated.…”
mentioning
confidence: 92%